2008
DOI: 10.1104/pp.107.113274
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Membrane-Anchored Fluorescent Protein Fusion Illuminates Sieve Element Plasma Membranes in Arabidopsis and Tobacco    

Abstract: Rapid acquisition of quantitative anatomical data from the sieve tubes of angiosperm phloem has been confounded by their small size, their distance from organ surfaces, and the time-consuming nature of traditional methods, such as transmission electron microscopy. To improve access to these cells, for which good anatomical data are critical, a monomeric yellow fluorescent protein (mCitrine) was N-terminally fused to a small (approximately 6 kD) membrane protein (AtRCI2A) and stably expressed in Arabidopsis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 57 publications
(81 reference statements)
2
45
0
Order By: Relevance
“…Measurements of 20 sieve plates (from at least two stems in each of two separate preparations) gave pore diameters between 0.30 and 0.55 mm. These data accord well with previous estimates for Arabidopsis stems of approximately 0.5 mm (1-week-old stems; Truernit et al, 2008) and 0.52 mm (stems of unspecified age; Thompson and Wolniak, 2008). By contrast, although pore numbers per sieve plate were approximately the same as in wild-type plants, sieve plate pores in stems of mutant plants appeared much smaller in diameter than those in wild-type plants.…”
Section: Loss Of Gsl7 Eliminates Callose From Phloem Sieve Platessupporting
confidence: 81%
“…Measurements of 20 sieve plates (from at least two stems in each of two separate preparations) gave pore diameters between 0.30 and 0.55 mm. These data accord well with previous estimates for Arabidopsis stems of approximately 0.5 mm (1-week-old stems; Truernit et al, 2008) and 0.52 mm (stems of unspecified age; Thompson and Wolniak, 2008). By contrast, although pore numbers per sieve plate were approximately the same as in wild-type plants, sieve plate pores in stems of mutant plants appeared much smaller in diameter than those in wild-type plants.…”
Section: Loss Of Gsl7 Eliminates Callose From Phloem Sieve Platessupporting
confidence: 81%
“…It is discussed whether the transport of the membrane-anchored protein occurs through the desmotubules connecting the ER network of the companion cells and the sieve elements followed by additional vesicular transport to the sieve element PM. Fluorescence of the membrane-anchored fusion protein is also detected in vesicle-like structures in the mature sieve elements (Thompson and Wolniak, 2008). A similar route is now suggested for the targeting of St SUT1.…”
Section: Oligomerization and Pm Targetingmentioning
confidence: 78%
“…In a recent study, it was shown that expression of a membrane-anchored fluorescent protein under control of the companion cell-specific At SUC2 promoter illuminates the sieve element PM in Arabidopsis and tobacco (Thompson and Wolniak, 2008). It is discussed whether the transport of the membrane-anchored protein occurs through the desmotubules connecting the ER network of the companion cells and the sieve elements followed by additional vesicular transport to the sieve element PM.…”
Section: Oligomerization and Pm Targetingmentioning
confidence: 99%
“…Resistant plants were validated visually and with PCR and named MM or DD, respectively. To create the pSUC2::MTI1 and pSUC2:: DEP1 constructs, MTI1 (1125 bp) and DEP1 (1524 bp) coding sequences (CDS) were amplified and inserted into pENTR/D-TOPO, which was recombined with a destination vector containing a 2125-bp-long fragment of the SUC2 promoter (pSUC2-dest; Thompson and Wolniak, 2008). The pSUC2::MTI1 and pSUC2::DEP1 constructs were introduced into mti1-1 and dep1-1 plants by floral dip, respectively, yielding the lines SM and SD.…”
Section: Construction Of Complementation Linesmentioning
confidence: 99%